Pendapat Muhammad Syahrur Tentang Poligami Serta Relevansinya Bagi Rencana Perubahan KHI - Firman Nurdiansyah (AL-HUKAMA, 2018)
One of the topics that continues to reap controversy is polygamy. In the Islamic world, polygamy is interpreted differently through its main source, the Qur’an. One of the Muslim thinkers who contributed to the interpretation in this matter was Muhammad Syahrur who used the boundary theory in seeing the case of polygamy. By observing the context of the verse as a whole, Syahrur emphasized that polygamy can only be done if the second wife and so on are widows and have orphans. This paper is a study of the thoughts of Muhammad Syahrur through his monumental work Al-Kitab Wa Al-Qur’an Qira’ah Mu’asirah and his other works. The thought of Muhammad Syahrur is described and then analyzed for its relevance to the amendment plan. Compilation of Islamic Law as a material law in deciding polygamy issues. The requirement for polygamy must be with widows with orphans as a valuable input for KHI, which has included the conditions for polygamy which have departed from the shortcomings and weaknesses of women, a requirement considered by feminist as a gender bias.